Prevalencia de desgaste profesional y psicomorbilidad en médicos de atención primaria de un área sanitaria de Madrid - Molina Siguero, A. (Aten Primaria, 2003)
AIM: To analyze worker burnout and the prevalence of psychiatric illness among primary care physicians, and to determine how burnout is related with sociodemographic and work-related factors. DESIGN: Cross-sectional, descriptive study SETTING: Primary care centers in Area 8, Madrid (central Spain). SUBJECTS: All 244 physicians (family medicine and pediatrics) who provided care at centers in Area 8 at the time of the study. METHOD: Anonymous, self-administered questionnaire that included the Maslach Burnout Inventory (worker burnout); GHQ-28 (possible mental illness); survey of sociodemographic and work-related factors, unhealthy behaviors, use of medications, and perceived quality of care and risk of medical errors in relation with work-related pressures; open question regarding causes of work-related stress. RESULTS: Response rate, 80.3%. Burnout was detected in 69.2% of the physicians (95% CI, 62.1%-75.4%) and was severe in 12.3%. The prevalence of possible psychiatric illness was 36.7%. Burnout was found to be related with possible psychiatric illness (P<.01); perception that work-related pressures frequently led to diminished quality of care and medical errors (P<.01); permanent employment status (P<.05); more than 1700 patients on the patient list (P<.05); age between 37 and 46 years (P<.01) and patient load of 35 to 47 patients/day (P<.05). CONCLUSIONS: The prevalence of worker burnout and possible psychiatric illness was high, and the two variables were related. A large percentage of participants perceived that work-related pressures diminished the quality of care provided.